From Intuitive Programming of Robotic Systems to Business Sustainability of Manufacturing SMEs - Bogdan Mocan; Mircea Fulea; Marieta Olaru; Melanie Buchmüller (Amfiteatru Economic Journal, 2016)
Economic growth and sustainable development are issues which are becoming more and more important for nowadays companies. Sustainable development strives for moderate and responsible use within the economic and production activity the limited resources of our planet. Eco-innovations, eco-efficiency and corporate social responsibility practices define much of the current industrial sustainability agenda. While important, they are insufficient in themselves to deliver the holistic changes necessary to achieve long-term social and environmental sustainability. This paper proposed a framework for designing multimodal human-robot interfaces and a demonstrator that facilitate a sustainable use of robotic systems with positive effects on SMEs business sustainability. The proposed approach is intended to bring important contributions to the development of human robot interaction in order to facilitate intuitive programming and to enable easily adapting to changes in robot tasks and applications without the need of using skilled personnel. Our research emphasize the idea that new technologies in product and process create and enable new business strategies; and we demonstrate that changing the paradigm in programming industrial robotic systems it is possible by a "business case for sustainability" to have a sustainable development of the business, in special in case of SMEs.
Keywords: O14; O33; 330; intuitive programming of robotic systems; business case for sustainability; sustainable production